2019
DOI: 10.1016/j.immuni.2019.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 and Related Cytokines in the Regulation of Inflammation and Immunity

Abstract: Forty years after its naming, interleukin-1 (IL-1) is experiencing a renaissance brought on by the growing understanding of its context-dependent roles and advances in the clinic. Recent studies have identified important roles for members of the IL-1 family-IL-18, IL-33, IL-36, IL-37, and IL-38-in inflammation and immunity. Here, we review the complex functions of IL-1 family members in the orchestration of innate and adaptive immune responses and their diversity and plasticity. We discuss the varied roles of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
600
1
13

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 729 publications
(680 citation statements)
references
References 207 publications
8
600
1
13
Order By: Relevance
“…Inflammasomes play an important role in innate immunity, where IL-1β, IL-18 and alarmins (e.g. IL-1α and HMGB1) help promote inflammation, neutrophil recruitment and an adequate adaptive immune response (Mantovani, Dinarello, Molgora, & Garlanda, 2019), while pyroptosis eliminates intracellular bacterial replicative niches . The antibacterial function of inflammasomes is illustrated by the ability of various inflammasome sensor proteins to recognise and respond to bacterial ligands (Eldridge & Shenoy, 2015;Hayward et al, 2018), and the increased susceptibility to infection shown by mice with deletions in inflammasome components (Man, Karki, & Kanneganti, 2017;Lacey & Miao, 2019).…”
Section: Signals For Inflammasome Activationmentioning
confidence: 99%
“…Inflammasomes play an important role in innate immunity, where IL-1β, IL-18 and alarmins (e.g. IL-1α and HMGB1) help promote inflammation, neutrophil recruitment and an adequate adaptive immune response (Mantovani, Dinarello, Molgora, & Garlanda, 2019), while pyroptosis eliminates intracellular bacterial replicative niches . The antibacterial function of inflammasomes is illustrated by the ability of various inflammasome sensor proteins to recognise and respond to bacterial ligands (Eldridge & Shenoy, 2015;Hayward et al, 2018), and the increased susceptibility to infection shown by mice with deletions in inflammasome components (Man, Karki, & Kanneganti, 2017;Lacey & Miao, 2019).…”
Section: Signals For Inflammasome Activationmentioning
confidence: 99%
“…IL‐1 exists in two forms, IL‐1α and IL‐1β, both of which are synthesized as ~33‐kDa precursors that can be processed via proteolytic cleavage, to mature cytokines . Our focus is on IL‐1α, a key initiating pro‐inflammatory factor, implicated in the pathogenesis/progression of several major disorders, including cardiovascular disease, neural inflammation, inflammatory bowel disease, atherosclerosis, and cancer .…”
Section: Interleukin‐1 a Pivotal Cytokine Of The Innate Immune Systemmentioning
confidence: 99%
“…7 IL-1 exists in two forms, IL-1α and IL-1β, both of which are synthesized as ~33-kDa precursors that can be processed via proteolytic cleavage, to mature cytokines. 8 Our focus is on IL-1α, a key initiating pro-inflammatory factor, implicated in the pathogenesis/progression of several major disorders, including cardiovascular disease, neural inflammation, inflammatory bowel disease, atherosclerosis, and cancer. Constitutively expressed by many cells, hematopoietic and non-hematopoietic, IL-1α is referred to as an "alarmin," rapidly upregulated following exposure to an array of DAMPs that are exposed during oxidative stress, cellular necrosis, ischemia-reperfusion injury, radiation, and other so-called "sterile" injuries.…”
Section: Interleuk In -1 a Pivotal C Y Tok Ine Of The Innate Immumentioning
confidence: 99%
“…Prior studies have shown that aging, radiation and chronic inflammation promote HSPC differentiation at the expense of self-renewal (Fleenor et al, 2015a;Mejia-Ramirez and Florian, 2020;Pietras, 2017). The pro-inflammatory cytokine, interleukin-1 (IL-1) is important in regulating hematopoiesis and the immune response in the acute setting but can drive pathology in the chronic setting (Mantovani et al, 2019).…”
Section: Introductionmentioning
confidence: 99%